2008
DOI: 10.1108/03090560810877132
|View full text |Cite
|
Sign up to set email alerts
|

Forecast competitor service strategy with service taxonomy and CI data

Abstract: Purpose -The paper aims to develop a service taxonomy model and a mathematical process to forecast a competitor's service business strategy in a multiple service business context by inputting CI data such as the profits of existing core services. Design/methodology/approach -A qualitative method of literature review is adopted to build a service taxonomy model and form two propositions. Based on the multiple business process integration concept of the resource-based view, a mathematical process constituted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Conversely, literature with scaffolding in information systems and decision support, fueled by the desire of bridging the gap between the business user and BI transformation and usage, criticized the firms’ focus on collection over analysis despite the challenge of information overload and gave significant attention to testing in-house acquisition techniques of BI collection to curb the exorbitant price of third-party sources by proposing Limited Information NBD/Dirichlet (LIND) models to infer key competitive measures based on site-centric data (Zheng et al , 2012) or two level conditional random fields (CRF) models to extract comparative relation features from entities and words (Xu et al , 2011) or event detection (NEED) applications that perform events detection based on properties extracted from news stories (Wei and Lee, 2004) or proposed 80/20 rule-based models for reduction of cycle time (Kohavi et al , 2002; Liu and Wang, 2008) or suggested data slicing and dicing technologies, which index and analyze documents collected from websites matching users’ interest (Chen et al , 2002) or grant rapid access displays of data (Walters et al , 2003). One commonality within this research stream is the evaluation of the proposed tool against the commercial engines (Chen et al , 2002; Zheng et al , 2012; Xu et al , 2011).…”
Section: Literature Synthesismentioning
confidence: 99%
“…Conversely, literature with scaffolding in information systems and decision support, fueled by the desire of bridging the gap between the business user and BI transformation and usage, criticized the firms’ focus on collection over analysis despite the challenge of information overload and gave significant attention to testing in-house acquisition techniques of BI collection to curb the exorbitant price of third-party sources by proposing Limited Information NBD/Dirichlet (LIND) models to infer key competitive measures based on site-centric data (Zheng et al , 2012) or two level conditional random fields (CRF) models to extract comparative relation features from entities and words (Xu et al , 2011) or event detection (NEED) applications that perform events detection based on properties extracted from news stories (Wei and Lee, 2004) or proposed 80/20 rule-based models for reduction of cycle time (Kohavi et al , 2002; Liu and Wang, 2008) or suggested data slicing and dicing technologies, which index and analyze documents collected from websites matching users’ interest (Chen et al , 2002) or grant rapid access displays of data (Walters et al , 2003). One commonality within this research stream is the evaluation of the proposed tool against the commercial engines (Chen et al , 2002; Zheng et al , 2012; Xu et al , 2011).…”
Section: Literature Synthesismentioning
confidence: 99%
“…The common theme across publications in the CI cluster (Quadrant 3, Figure 1) is the use of eclectic definitions of intelligence concepts that fall into two research streams: CI as a product and CI as a process. The former regards CI as the final intelligence or knowledge delivered to the business user (Chen et al, 2002;Xu et al, 2011;Zheng et al, 2012); the latter considers it a sequential activity through which it funnels intelligence to support organizational objectives (Dishman and Calof, 2008;Liu and Wang, 2008;Wright et al, 2009) and whose budgeting enhances organizational vigilance against environment uncertainty (Opait et al, 2016).…”
Section: Competitive Intelligence Clustermentioning
confidence: 99%
“…For the purpose of building a mathematical model for service business analysis, we adopted the 3P + C (provider, process, place, and customer) service classifying model proposed by Liu and Wang (2008). Liu and Wang (2008) classify the structures of the previous classifications of services based on the schemes concepts, i.e. discrete item scheme, continuum scheme, and matrix scheme.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu and Wang (2008) have analyzed the advantages and disadvantages of the three schemes but without listing the related literatures of them. Main researchers of the service classifications in continuum and matrix schemes are listed in Tables I and II, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%